Technical Debt Management in Brazilian Software Organizations: A Need, an Expectation or a Fact? - Silva, Victor; Jeronimo, Helvio; Travassos, Guilherme Horta (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Maintenance is often the most expensive and time-consuming of all software system lifecycle phases. Technical Debt (TD) refers to technical decisions on shortcuts and workarounds taken during the software development. It affects the internal quality of software. Therefore, software maintenance can be difficult when the TD is not perceived or managed in the projects. Despite the increasing attention of practitioners and researchers, TD studies indicate its management (TDM) is still incipient. Particularly in Brazilian Software Organizations (BSOs), there is still a lack of information on how practitioners perceive and manage the TD in software projects. This paper reports the results of two studies aiming to investigate the current knowledge level of practitioners from BSOs regarding TD and TDM, and to produce a summary of the available technologies to manage TD. To achieve these objectives, we surveyed practitioners from BSOs and undertook a quasi-Systematic Literature Review (qSLR) to gather specific TDM technologies. The survey results indicated that the general BSOs practitioners' knowledge regarding TD and TDM is still low. Few participants from the survey reported managing TD. The qSLR results provide evidence-based information about a set of TDM technologies, synthesized in evidence briefings to facilitate their use by software practitioners in the industry. Moreover, this paper offers links to a research package to aid in the replication process and support future investigations.